Różne przejawy cenzury wobec serialu Dom Jana Łomnickiego - Śmiałowski, Piotr (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
The historical series Home (1980–2000), which took 20 years in the making, provides excellent material for analyzing how censorship functioned at sensitive moments in history. The first seven episodes of Home were created before August 1980, the next five during the period of Solidarity domination and after the introduction of martial law. Although the temporal distance is small, it is clear that the episodes shot in the 1980s belong to three different eras. In the article, I compare two groups of sources regarding the censorship of this series. On the one hand, I refer to the documents prepared by the television and cinema authorities, which constituted the official interpretation of the interference. On the other hand, I quote the creators’ memoirs, commenting on the restrictions affecting Home. Various types of censorship emerge from this: from obvious ones, involving interference with the text of the script and the finished film material, through attempts to broadcast Home without some episodes, to intentions to make cuts without the consent of the authors.